A Randomized Trial of Nighttime Physician Staffing in an Intensive Care Unit - Kerlin, Meeta Prasad; Small, Dylan S; Cooney, Elizabeth; Fuchs, Barry D; Bellini, Lisa M; Mikkelsen, Mark E; Schweickert, William D; Bakhru, Rita N; Gabler, Nicole B; Harhay, Michael O; Hansen-Flaschen, John; Halpern, Scott D (The New England journal of medicine, 2013)
In this single-center, controlled trial at a U.S. academic medical center, investigators found that having in-house intensivists available at night did not have a significant effect on the length of stay in the ICU. Most studies suggest that intensivist physicians improve patient outcomes in intensive care units (ICUs). 1 – 3 It is thus tempting to conclude that a “dose–response effect” might exist, such that greater exposure to intensivists would be associated with even better outcomes. 4 Indeed, some authors argue that 24-hour presence of seasoned intensivists at the bedside of patients would improve diagnostic and therapeutic efficiency, particularly for high-risk patients. 5 – 7 As a result, many ICUs, including one third of academic ICUs in the United States 8 and nearly three quarters of ICUs in Europe, 9 , 10 use in-hospital intensivist staffing at night. Before-and-after studies of nighttime . . .